A survey of the disaster management and recovery preparedness of the National Archives of the Philippines - Tiangco, Blas Ople G.; Arlante, Salvacion M. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2000)
The field of archival management, in relation to conservation, preservation and restoration has yet to be fully recognized in our country. And in line with the growing volume of archives, there has been no attempt to conduct a survey of disaster management and recovery preparedness.
The National Archives was chosen to survey and study. The main objective was to determine if there was an existing disaster management and recovery program. Did the National Archives, better known as the Records Management and Archives Office have guidelines in disaster management? What techniques do they have in recovering damaged documents in an event of a disaster?
The primary significance of study is that it is an exploratory study. The field of disaster management has yet to be understood of its implications to archival management in our country. It is a pioneering study in this area and can be used as a springboard for further and detailed studies in archival preservation and conservation.
In-depth interviewing, participant observation and questionnaires were used for data gathering. It was discovered that the RMAO has no disaster management plan. There is no recovery management plan either.
This was widely attributed to five factors that affect the implementation of a disaster management and recovery plan. These are (1) Awareness of the importance of archives (2) Lack of information on the importance of disaster preparedness and recovery (3) Lack of support (4) Lack of funding and (5) Too much politics. Of the five, the fifth being the biggest factor to a lack of support and funding. Support here is used as a term related to manpower, since there are only a few people who are working in the archives and technical services (preservation department) of the National Archives.
The recommendation part of this study was then devoted on how to formulate a disaster management plan, with a sample plan as an appendix. This was also based from the information gathered from studying the collection that ranged from books, paper documents, microfilm, photographs, blue prints and CD-ROMS.
Vita.
Thesis (Bachelor of Library and Information Science)
Keywords: Archives -- Philippines; Disasters; Emergency management